2022
DOI: 10.3389/fped.2022.860789
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spirulina Chikki Supplementation on Nutritional Status of Children: An Intervention Study in Tumkur District of Karnataka, India

Abstract: ObjectiveTo assess the impact of Spirulina Chikki supplementation on the nutritional status of children (6 months−6 years).DesignA cross-sectional study design was adopted to assess the changes in nutritional status among the children (after 12 months of intervention period). The bassline and endline assessment were carried out from September 2020 to August 2021, respectively.SettingTotal 106 villages (108 Anganwadi Centers in nine circles) from Tumkur District were covered.MethodsChildren aged 6 months−6 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Low- and middle-income countries also have a high proportion of malnourished children. Considering 106 villages from Tumkur District of Karnataka state in India, Kashyap et al found a significant decline in the prevalence of severe wasting and stunting with an overall improvement in the nutritional status among the children of 6 months to 6 years of age who consumed the spirulina chikki/granules supplementation for longer duration ( 9 ). Implementing such nutritional intervention in the targeted geographical areas with a higher prevalence of malnourishment in low- and middle-income countries is a commendable step to harmonize wellbeing.…”
Section: Contribution To the Fieldmentioning
confidence: 99%
“…Low- and middle-income countries also have a high proportion of malnourished children. Considering 106 villages from Tumkur District of Karnataka state in India, Kashyap et al found a significant decline in the prevalence of severe wasting and stunting with an overall improvement in the nutritional status among the children of 6 months to 6 years of age who consumed the spirulina chikki/granules supplementation for longer duration ( 9 ). Implementing such nutritional intervention in the targeted geographical areas with a higher prevalence of malnourishment in low- and middle-income countries is a commendable step to harmonize wellbeing.…”
Section: Contribution To the Fieldmentioning
confidence: 99%
“…It is known to contain various functional compounds such as beta-carotene, phycocyanin, tocopherols, polyunsaturated fatty acids, particularly gamma-linolenic acid and phenolic compounds (13). Initially, the nutritional properties of Spirulina were recognized by various intergovernmental institutions to fight against malnutrition in 1970 (14). In 1996, World Health Organization (WHO) declared spirulina to be the best food for the future owing to its rich protein and antioxidant properties (15).…”
Section: Introductionmentioning
confidence: 99%